The Effect of Using New American Lecture Strategy on Students’ Reading Comprehension - Dahler Dahler; Novia Ayu Trisma Y. (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
The purpose of this research was find out whether there is any significant difference of using New American Lecture strategy on students’ reading comprehension in narrative text at State Junior High School 1 Tanah Putih Rokan Hilir Regency. The number of respondents of this research was 50 students. They were required to answer the question provided by the researcher. To analyze the data, the researcher applied Independent sample T-test and paired Sample T-test formula through SPSS 16. However, the type of this research was quasi-experimental design. After analyzing the data, the researcher found that there was a significant difference of using New American Lecture strategy strategy on students’ reading comprehension in narrative text at State Junior High School 1 Tanah Putih Rokan Hilir Regency, where Paired sample T-test shows 11.308 in the significant level 5% was 2.01, and in the level 1% was 2.80. Then alternative hypothesis (Ha) was accepted. which was shown by 2.01<11.308> 2.68.